Trends and drivers of skilled birth attendant use in Nigeria (1990–2013): policy implications for child and maternal health - Fagbamigbe AF; Hurricane-Ike EO; Yusuf OB; Idemudia ES (Dove Medical Press, 2017)
Adeniyi F Fagbamigbe,1,2 Elizabeth O Hurricane-Ike,3 Oyindamola B Yusuf,1 Erhabor S Idemudia2 1Department of Epidemiology and Medical Statistics, Faculty of Public Health, College of Medicine, University of Ibadan, Ibadan, Nigeria; 2School of Research and Postgraduate Studies, Faculty of Human and Social Sciences, North West University, Mafikeng, South Africa; 3Department of Demography and Social Statistics, Obafemi Awolowo University, Ile Ife, Nigeria Introduction: While Nigeria accounts for only 2% of the world population, it regrettably shares 14% of global maternal death burden. Whether its reported increase in antenatal care utilization is accompanied by increased use of skilled birth attendants (SBAs) is not known. This study assessed trends in utilization of SBAs in Nigeria between 1990 and 2013 and identified its determinants.Methods: Data from four consecutive Nigerian Demographic and Health Survey reports between 1990 and 2013 were pooled. We used basic descriptive statistics, test of association, and logistic regression to assess the prevalence, relative change, and determinants of SBA use at 5% significance level. Sample weights were applied, and adjustment was made for survey design and sampling errors.Results: Nearly half (46.7%) of the respondents were aged 25–34 years, while half (50.3%) of the respondents had no formal education. The prevalence of SBA use increased only marginally across the years and characteristics studied, from 32.4% in 1990 to 38.5% in 2013, an insignificant 6% increase. Educated women used SBA more than women with no education (92.4% vs 13.1%), and their odds ratio of using SBA were thrice that of uneducated women (odds ratio =3.09, 95% confidence interval =2.17–4.38). Women involved in decisions regarding their use of health facility were 12% more likely to use SBAs than others who do not. Educational attainment, religion, tribe, rural/urban residence, and zone of residence were significant to the use of SBA.Conclusion: The use of SBA was very low throughout the study period, barely at one third usage with insignificant changes over the studied period. Women empowerment, including decision-making power and residence, were the strongest determinants of SBA use. To overturn poor child and maternal health outcomes in Nigeria through SBA use, efforts should be targeted at educating girls, sexual and reproductive health education, and accessible and improved health care facility services. Keywords: antenatal care, utilization, women education, Nigeria, women empowerment, DHS